A hepatic stellate cell gene expression signature associated with outcomes in hepatitis C cirrhosis and hepatocellular carcinoma after curative resection. Issue 10 (4th June 2015) - Zhang, David Y; Goossens, Nicolas; Guo, Jinsheng; Tsai, Ming-Chao; Chou, Hsin-I; Altunkaynak, Civan; Sangiovanni, Angelo; Iavarone, Massimo; Colombo, Massomo; Kobayashi, Masahiro; Kumada, Hiromitsu; Villanueva, Augusto; et al.
Abstract : Objective: We used an informatics approach to identify and validate genes whose expression is unique to hepatic stellate cells and assessed the prognostic capability of their expression in cirrhosis. Design: We defined a hepatic stellate cell gene signature by comparing stellate, immune and hepatic transcriptome profiles. We then created a prognostic index using a combination of hepatic stellate cell signature expression and clinical variables. This signature was derived in a retrospective–prospective cohort of hepatitis C-related early-stage cirrhosis (prognostic index derivation set) and validated in an independent retrospective cohort of patients with postresection hepatocellular carcinoma (HCC). We then examined the association between hepatic stellate cell signature expression and decompensation, HCC development, progression of Child–Pugh class and survival. Results: The 122-gene hepatic stellate cell signature consists of genes encoding extracellular matrix proteins and developmental factors and correlates with the extent of fibrosis in human, mouse and rat datasets. Importantly, association of clinical prognostic variables with overall survival was improved by adding the signature; we used these results to define a prognostic index in the derivation set. In the validation set, the same prognostic index was associated with overall survival. The prognostic index was associated with decompensation, HCC and progression of Child–Pugh class in the derivation set, and HCC recurrence in the validation set. Conclusions: This work highlights the unique transcriptional niche of stellate cells, and identifies potential stellate cell targets for tracking, targeting and isolation. Hepatic stellate cell signature expression may identify patients with HCV cirrhosis or postresection HCC with poor prognosis.